VARIABILITY AND MODIFICATION OF PROVERBS IN THE BULGARIAN MASS MEDIA : A SYSTEMATIC APPROACH - Vager, Marina (Proverbium - Yearbook, 2015)
The present research deals with the variability and modification of Bulgarian proverbs in terms of a systematic approach in linguistics. A detailed analysis of proverb usage in the mass media shows that a proverb system undergoes both quantitative and qualitative alterations (in Aristotle’s sense), quantitative alterations resulting from proverb variability, qualitative alterations from proverb transition to a phraseme and unproverbial application of a proverb to the mass media. Proverb variability is regarded in the paper as a mechanism of a proverb system to renovate itself, while proverb modification is a mechanism of proverb transition to another linguistic unit. Following the mechanism of proverb variability, new variants of proverbs and new potential prov-erbs are created within the discourse of the mass media. The linguistic and stylistic means of proverb variability and modification are examined in the paper. The study strives to provide a theoretical foundation for the key notions of proverb variability, modification, proverb variant, variation and invariant, as used in the present paper.